Suatu Tinjauan Tentang Perpustakaan Sekolah Sebagai Penunjang Kegiatan Belajar-Mengajar di SMKN 5 Padang - Ariani, Tri Bery; Nst., Bakhtaruddin (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
This paper focuses on a review of the school library to support teaching and learning activities at SMKN 5 Padang. This study aimed to describe: (1) a review of the school library to support teaching and learning activities at SMKN 5 Padang, (2) the constraints that inhibit an overview of school libraries in supporting teaching and learning activities at SMKN 5 Padang. Data were collected through observation and interviews with the head librarian at SMKN 5 Padang. Object of study of this thesis paper is the role of the school library at SMK 5 Padang. The data were analyzed descriptively. Based on data analysis, it can be concluded that the role of school libraries in supporting teaching and learning activities at SMKN 5 Padang this is not optimal due to inadequate facilities, the number of library managers were not enough human resources to manage and develop the library as a learning resource for students and teachers less professional, a collection of reading materials in the school library less complete, as well as the students' interest in school libraries are very less. Keywords: school libraries; role of the school library; teaching and learning activities